EquiFrame: A framework for analysis of the inclusion of human rights and vulnerable groups in health policies. - MANNAN, HASHEEM; MAC LACHLAN, MALCOLM (My University, 2011)
Ensuring that health policies uphold core concepts of human rights and are inclusive of vulnerable groups are imperative aspects of providing equity in health care, and of realizing the United Nations? call for Health for All. We outline the process of extensive consultation undertaken across countries and stakeholders culminating in the development of EquiFrame, in conjunction with its associated definitions of core concepts of human rights and vulnerability. EquiFrame is a systematic policy analysis framework that assesses the degree to which 21 core concepts of human rights and 12 vulnerable groups are mentioned and endorsed in health policy documents. We illustrate the scope of the framework by reporting the results of its application to two health policy documents from (Northern) Sudan: the rather generalist Health Policy of (Northern) Sudan, and the more specific National Drug Policy of (Northern) Sudan. We outline some limitations of the framework and highlight issues for consideration in its interpretation. EquiFrame offers a systematic approach to analyzing and facilitating the inclusion of core concepts of human rights and vulnerability in existing or developing health policies and ultimately to promoting greater equity in health care.
PUBLISHED
Corresponding author
Keywords: Health Policy Analysis; Human Rights; EquiFrame; EquitAble